1999
DOI: 10.1002/(sici)1097-0142(19990401)85:7<1439::aid-cncr3>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Staining of interleukin-10 predicts clinical outcome in patients with nasopharyngeal carcinoma

Abstract: BACKGROUND Interleukin‐10 (IL‐10) has been implicated as an important modulator of lymphoid cells, and its sequence is homologous to an open reading frame in the Epstein–Barr virus (EBV) genome. Nasopharyngeal carcinoma (NPC) is a representative tumor related to EBV infection. METHODS The authors investigated the expression of IL‐10 in 21 primary NPCs by using an immunohistochemical approach to examine its prognostic significance. RESULTS IL‐10 staining was positive in 12 of 21 primary NPCs (57%). There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In a previous study of immunoglobulin Amediated EBV infection, GM-CSF expression in NPC cells is increased at the initial infection stage, where the viral lytic cycle may occur (40). On the other hand, in a previous study examining IL-10 expression in NPC biopsy specimens, IL-10 is not always detectable in tumor cells but is generally detectable among tumor-infiltrating mononuclear cells, which may include lymphocytes and monocytes (19). Even though the clues are very limited, our findings draw attention to the potential contribution of EBV reactivation to local immunosuppression of NPC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous study of immunoglobulin Amediated EBV infection, GM-CSF expression in NPC cells is increased at the initial infection stage, where the viral lytic cycle may occur (40). On the other hand, in a previous study examining IL-10 expression in NPC biopsy specimens, IL-10 is not always detectable in tumor cells but is generally detectable among tumor-infiltrating mononuclear cells, which may include lymphocytes and monocytes (19). Even though the clues are very limited, our findings draw attention to the potential contribution of EBV reactivation to local immunosuppression of NPC.…”
Section: Discussionmentioning
confidence: 90%
“…The functional inactivation of immune cells in NPC tumors may be attributed to several suppressive mechanisms in the microenvironment, including IL-10, gelactin-9, and regu-latory T cells (33,36,61). Notably, IL-10 has been associated with poor prognosis of NPC, suggesting that it may blunt not only antivirus but also anticancer immune responses in the tumors (19).…”
mentioning
confidence: 99%
“…Furthermore, murine plasmacytomas treated with antisense IL-10 are more immunogenic than the parental cell lines (18). IL-10 has been detected in biopsy specimens of human carcinomas and gliomas in association with more aggressive tumor growth and shorter survival times (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of IL-10 have been reported in patients with head and neck carcinomas, including NPC [14][15][16]. Clinical evidence has also suggested that the expression of IL10 might influence treatment outcomes in NPC patients [17]. The human IL10 gene, composed of five exons and four introns, is mapped to chromosome 119 between 1q31 and 1q32, which displays three common polymorphisms in the gene promoter region: -1082 A/G (rsl800896), -819 T/C (rsl800871), and -592C/A (rsl800872).…”
Section: Introductionmentioning
confidence: 99%